Description of Blood Glucose Levels in Hypertension Patients using the Point Of Care Test Method In Cilame Village - Rahmatulloh, Rahmatulloh; Sudrajat, Agus (Journal of Scientific Insights, 2024)
Description of Blood Glucose Levels in Hypertension Patients using the POCT (Point Of Care Test) Method In Cilame Village. Non-communicable diseases (NCDs) are diseases that are not infectious And can infectious to a person through contact whatever, for example, pressure blood tall. Hypertension is defined as experiencing increased pressure blood systolic as big as 140 mmHg or more and pressure blood diastolic as big as 90 mmHg or more. Pressure blood long-term (chronic) can cause resistance to insulin. When You suffer insulin resistance, glucose piles up in in blood instead absorbed by cells, Which can cause diabetes. Sugar blood is monosaccharides, carbohydrates main Which work as a source of energy in the body. The objective study is To know the status rate of sugar blood in patients with hypertension with the use method POCT. Type study This is descriptive And cross-sectional. Method POCT will used as a method of taking samples. Amount respondents was as many as 30 people. Results survey based on characteristics show that respondents suffered hypertension on age mature most (20-59 years): 20 people, Women: 22 people, And history short hypertension (1-5 years): 22 people. Sugar blood normal And pressure blood high. Conclusion: From the results control sugar blood at 3 0 respondents, 18 people have a rate sugar blood and 12 people have a rate sugar blood normal.